2017
DOI: 10.1007/s00393-017-0283-7
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 7 gene single nucleotide polymorphisms and the risk for systemic lupus erythematosus: a case-control study

Abstract: Regarding rs3853839, there was a statistically significant difference in the distribution of the genotypes between SLE patients and the control group in our study (P = 0.009). A significant association was detected between TLR7 genotypes (rs385389) and lupus nephritis (p = 0.021). Regarding rs179019, there was no statistically significant difference in the distribution of the genotypes between SLE patients and the control group in our study (P = 0.271) CONCLUSION: This study revealed the plausible role of TLR7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
1
10
1
Order By: Relevance
“…Among these are TLR7 SNPs, and studies have suspected their potential in progression of different malignancies, and moreover, these SNPs are suggested to predict the response outcome to anti-cancer therapies [25]. In line with these suggestions, the present study examined an intron region of TLR7 gene [26] and enterovirus 71 [27] infections and two autoimmune diseases, systemic lupus erythematosus (SLE) [28,29] and Graves' disease [30]. No clear effect was presented regarding viral infections or Graves' disease, while contradicting results were found in SLE.…”
Section: Discussionmentioning
confidence: 84%
“…Among these are TLR7 SNPs, and studies have suspected their potential in progression of different malignancies, and moreover, these SNPs are suggested to predict the response outcome to anti-cancer therapies [25]. In line with these suggestions, the present study examined an intron region of TLR7 gene [26] and enterovirus 71 [27] infections and two autoimmune diseases, systemic lupus erythematosus (SLE) [28,29] and Graves' disease [30]. No clear effect was presented regarding viral infections or Graves' disease, while contradicting results were found in SLE.…”
Section: Discussionmentioning
confidence: 84%
“…The number of SLE patients with current renal involvement was higher in SLE TLR7 hi group, which, might be due to increased anti-DNA and RNA/RNP Abs and, the formation of immune complexes. Two recent studies show an association between TLR7 rs3853839 G risk allele and the development of lupus nephritis or other manifestations of SLE, including malar rash, photosensitivity, pericardial effusion, reduced complement, and anti-dsDNA and anti-Sm auto-Abs (23, 59).…”
Section: Discussionmentioning
confidence: 99%
“…However, TLR7 may be an interesting gene for future studies given that an additional moderately associated SNP was found in this gene. Other SNPs in this gene have been linked to the antibody‐mediated autoimmune diseases, systemic lupus erythematosus (SLE) (Kawasaki et al , ; Enevold et al , ; Wang et al , ; Raafat et al , ) and Graves disease (Xiao et al , ). Moreover, this gene shows copy number variation (CNV) that has been linked to SLE (Garcia‐Ortiz et al , ; Pacheco et al , ) and Behçet Disease (Fang et al , ).…”
Section: Discussionmentioning
confidence: 99%